Liquid L-T4 therapy in hypothyroid patients with gastric diseases, an observational study - Poupak Fallahi; Francesca Ragusa; Armando Patrizio; Valeria Mazzi; Chiara Botrini; Giusy Elia; Eugenia Balestri; Emilio Barozzi; Licia Rugani; Elena Palmisano; Maria Carla Cosenza; Gilda Varricchi; et al. (Frontiers in Endocrinology, 2024)
IntroductionThis is an observational and retrospective study, in which we have analyzed data from patients affected by gastric diseases (p) who have been treated with liquid L-T4 (L-LT4;84 p), or tablet L-T4 (T-LT4;120 p), for the replacement therapy of hypothyroidism. The aim of the study is to compare the stability of TSH [normal range, 0.3-3.5 μIU/ml] in these patients.MethodsAll p assumed L-T4 30 minutes before breakfast. The types of gastric disease were: a) T-LT4 group: 74 chronic gastritis (CG); 4 gastrectomy for gastric cancer (GTx); 42 gastro-plastics (GP); b) L-LT4 group: 60 CG; 3 GTx; 21 GP (p>0.05). 66% p in T-LT4 group were chronically treated with proton pump inhibitors (PPI), against 51% in L-LT4 group (p>0.05). The frequency of Helicobacter Pylori infection was 17% in both T-LT4 and L-LT4 groups. The gender distribution, mean age and body weight were similar in the 2 groups (p>0.05). The mean L-T4 dosage in T-LT4 group at the basal evaluation was 1.22+/-0.27 μg/kg/die, in the L-LT4 group 1.36+/-0.22 μg/kg/die (p>0.05).ResultsAt the basal evaluation the prevalence of patients with a TSH>3.5 μIU/mL in T-LT4 group was 36%, in L-LT4 group 46% (p<0.05). After adjustment of the dosage of the LT-4 therapy, the p were re-evaluated in an interval range of 5-9 months, for 4 times, during an overall period ranging from 23 to 31 months. At the first re-evaluation, the prevalence of p with a TSH>3.5 μIU/mL was 13% in both groups. At the second re-evaluation, the prevalence of p with a TSH>3.5 μIU/mL in T-LT4 group was 26%, in L-LT4 group 13% (p>0.05). At the third re-evaluation, the prevalence of p with TSH<3.5 μIU/mL in T-LT4 group was 19%, in L-LT4 group 9% (p=0.05). At the fourth and last re-evaluation, the prevalence of patients with a TSH>3.5 μIU/mL in T-LT4 group was 18%, in L-LT4 group 5% (p<0.05). Mean FT4 and FT3 circulating levels were not significantly different in the two group at each visit.DiscussionThese data suggest that the liquid L-T4 formulation therapy can result in a more stable control of TSH levels in hypothyroid patients with gastric disorders in the long-term follow-up.